DESIGN OF GEOTHERMAL POWER PLANT (GPP) BINARY CYCLE PIPING SYSTEM 10 MW CASE STUDY: ULUBELU AREA - Zahwa Efendi, Maulida
Indonesia is a country with the largest geothermal potential in the world. However, the utilization of geothermal energy in Indonesia is still not optimal because the majority of geothermal power plants (GPP) in Indonesia only utilize geothermal steam. Most of the geothermal wells are hydrothermal types, which are dominated by brine. Utilization of geothermal energy can be optimized by utilizing brine. That is, by making binary cycle geothermal power plants. The construction of the GPP binary cycle includes a new piping system for geothermal fluid and n-pentane as working fluid. In this thesis, the piping system design covers process analysis, hydraulic analysis, diameter selection, pipe thickness selection and its insulation, span calculation, and stress analysis to be built at the Ulubelu PLTP. The design is carried out based on the ASME B31.1 power piping code. Hydraulic analysis and diameter selection resulted in a net power of 10.57 MW from the simulation process at optimum operating conditions. Meanwhile, the selected pipe thickness based on the largest pipe thickness is uniform for each diameter, so that the pipe size is 16 sch. 20, 18 sch.20, 24 sch 20, and 12 sch.30. Then, the selected insulation thickness is 50 mm with calcium silicate material. In addition, the maximum span length is set at 10 m. The piping system has been modified by changing the type of support to have high stress resistance so that the system is safe from the stress due to sustain loads, thermal expansion loads, and occasional loads due to earthquakes and wind. The parameter studies show that failure in the piping system will occur when the earthquake load exceeds 0.33 g or the wind velocity exceeds 250 km/h.